Biomass-a Renewable Resource for Carbon Materials (2nd Edition) - Pulidindi, Indra; Sharma, Pankaj; Gedanken, Aharon (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The effort of the Editors has received global attention. Indebtedness is due to Saha and Asif and coworkers from Canada, Joseph and Mahapatra and coworkers from Poland and India, Ramirez-Montoya and coworkers from Spain and Mexico, Mota-Panizio and coworkers from Portugal and Brazil, Izquierdo and Lopez-Coca and coworkers from Spain, Vinitnantharat and coworkers from Thailand and the UK, Roy and Fini and coworkers from India and the USA, Lawson and Luyima and coworkers from Ghana and South Korea, Fouad El Mansouri and coworkers from Morocco and Spain, and Man Zhang and Yaning Zhang and coworkers from China for the 10 scholarly research papers dealing with the synthesis, characterization, properties, and applications of new carbon materials. The applications are mainly centered around environmental remediation owing to the intensity of the problem and comprise of water decontamination and the removal of heavy metals and organic compounds like tannic acid from contaminated sources. The use of biochar in agriculture for preventing nitrogen leaching for soil has also been included. Unconventional carbon-related materials like rice husk ash and carbon steel slag were also used for exotic applications.